Associations Between Trauma, Early Maladaptive Schemas, Personality Traits, and Clinical Severity in Eating Disorder Patients: A Clinical Presentation and Mediation Analysis - Meneguzzo, Paolo; Cazzola, Chiara; Castegnaro, Roberta; Buscaglia, Francesca; Bucci, Enrica; Pillan, Anna; Garolla, Alice; Bonello, Elisa; Todisco, Patrizia (Frontiers in Psychology, 2021)
The literature has shown a significant association between traumatic experiences and eating psychopathology, showing a greater symptomatology in patients with trauma history. Less is known about the associations between trauma and cognitive schemas, and personality traits and the differences between childhood and adulthood trauma experiences. Thus, this paper aims to assess the clinical and psychological characteristics of eating disorder (ED) patients, looking for differences between patients without a history of trauma and patients with trauma experiences, as well as at possible differences between exposure in childhood, adulthood, or repeated events. Another aim of the paper is to evaluate the possible mediation role of cognitive schemas and personality traits in the relationship between early trauma and eating psychopathology. From January to November 2020, 115 consecutive inpatients admitted for a specific multidisciplinary ED treatment in a dedicated Unit were evaluated for trauma, differentiating between trauma occurring in childhood and adulthood. The subjects were evaluated for early maladaptive schemas (EMS), personality traits, trauma symptomatology, quality of life, and specific psychopathologies linked to EDs. A mediation analysis between childhood trauma and eating psychopathology was performed, with EMS and personality traits as mediators. The physical and psychological symptomatology in patients with a history of trauma had higher scores in all the areas evaluated, and patients with both childhood and adulthood trauma exposure had more impaired clinical profiles. The mediation analysis showed a specific mediator role for the 'disconnection and rejection' EMS factor in the relationship between childhood trauma and eating psychopathology. Trauma experiences are associated with more severe clinical symptomatology in EDs and may need a specific assessment in patients with failed outpatient standard treatments. Specific cognitive schemas linked to disconnection and rejection domain should be evaluated in treatments for ED patients with history of trauma due to the mediation role between trauma and eating psychopathology. The need for outcome studies about treatment approaches for ED patients with history of trauma is discussed.